Effect of copper toxicity on the hemolymph factors of the Indian edibleoyster, Crassostrea madrasensis (Preston) - Gijo, Ittoopp; George, K C; Rani Mary, George; Sobhana, K S (Indian Journal of Fisheries, 2016)
The Indian edible oyster, Crassostrea madrasensis collected from the backwaters of Kochi, India were exposedto three sub-lethal concentrations of copper viz. 0.1, 0.5 and 1 ppm at a salinity of 12 ppt. Modulations indifferent heamolymph factors such as total hemocyte count, differential hemocyte count, phagocytosis, serumprotein, serum acid phosphatase, serum phenol oxidase and serum lysozyme were studied. It was found that, thelowest concentration of copper had a stimulating effect on all the parameters studied. However, at higherconcentrations except serum lysozyme all the hemolymph parameters studied showed significant reduction.Although copper could act as an immunostimulant at lower doses, it significantly reduced the disease resistanceof the species at concentrations above 0.5 ppm in mesohaline waters.